Human platelet antigens – 2013. Issue 2 (16th September 2013) - Curtis, B. R.; McFarland, J. G.
<x xml:space="preserve">Abstract</x> To date, 33 human platelet alloantigens (HPAs) have been identified on six functionally important platelet glycoprotein (GP) complexes and have been implicated in alloimmune platelet disorders including foetal and neonatal alloimmune thrombocytopenia (FNAIT), posttransfusion purpura (PTP) and multitransfusion platelet refractoriness (MPR). The greatest number of recognized HPA (20 of 33) resides on the GPIIb/IIIa complex, which serves as the receptor for ligands important in mediating haemostasis and inflammation. These include HPA‐1a, the most commonly implicated HPA in FNAIT and PTP in Caucasian populations. Other platelet GP complexes, GPIb/V/IX, GPIa/IIa and CD109, express the remaining 13 HPAs. Of the recognized HPAs, 12 occur as six serologically and genetically defined biallelic 'systems' where the –a form designates the higher frequency allele and the –b form, the lower. Twenty‐one other HPAs are low‐frequency or rare antigens for which postulated higher frequency –a alleles have not yet been identified as antibody specificities. In addition to the HPA markers, platelets also express ABO and human leucocyte antigen (HLA) antigens; antibodies directed at the former are occasionally important in FNAIT, and to the latter, in MPR.